World Class Sub District Model - Yusi Eva Batubara; Sadu Wasistiono (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
The concept of world-class government has been applied at the state level. Explicitly the political policies stipulated through Perpres No. 81 of 2010 there is no detailed roadmap for each government structure, let alone to the sub-district level. Given that there are no world class sub-district parameters, it is necessary to develop an initial concept by combining various policies with theory. This is in line with the determination of the Sumedang Regency Government to excel at the national level. This study uses the SWAR method, combining the concepts of SWOT and SOAR. The new concept generated in this study covers 11 aspects including: determining the model and sub-district; determination of the authority of the elected sub-district; determining the core business of the selected sub-district; determining the size of the selected sub-district budget; determining the form and organizational structure of the selected sub-district; determination of the number of ASN selected sub-districts; performance measurement of selected sub-districts; IT development in the sub-district; the leadership of the sub-district head in the selected sub-district; evaluation in selected sub-districts; roadmap to world-class district government.